Multiscale Problems in Science and Technology: Challenges to Mathematical Analysis and Perspectives - Antonić, Nenad 1962-; Duijn, Cornelis Johannes van; Jäger, Willi; Mikelić, Andro (Springer, 2002)
These are the proceedings of the conference "Multiscale Problems in Science and Technology" held in Dubrovnik, Croatia, 3-9 September 2000. The objective of the conference was to bring together mathematicians working on multiscale techniques (homogenisation, singular pertubation) and specialists from the applied sciences who need these techniques and to discuss new challenges in this quickly developing field. The idea was that mathematicians could contribute to solving problems in the emerging applied disciplines usually overlooked by them and that specialists from applied sciences could pose new challenges for the multiscale problems. Topics of the conference were nonlinear partial differential equations and applied analysis, with direct applications to the modeling in material sciences, petroleum engineering and hydrodynamics
Keywords: Konferenzschrift -- 2000 -- Dubrovnik; Mehrskalenanalyse